2004
DOI: 10.1369/jhc.4a6428.2004
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Visualization of the Microbial Glycocalyx with Low-voltage Scanning Electron Microscopy: Dependence on Cationic Dyes

Abstract: S U M M A R YThe microbial glycocalyx is composed of a variety of polyanionic exopolysaccharides and plays important roles in microbial attachment to different substrata and to other cells. Here we report the successful use of low-voltage scanning electron microscopy (LVSEM) to visualize the glycocalyx in two microbial models ( Klebsiella pneumoniae and Enterococcus faecalis biofilms) at high resolution, and also the dependence on fixation containing polycationic dyes for its visualization. Fixation in a paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 29 publications
2
139
1
Order By: Relevance
“…Introduction of the empty vector did not restore the aggregation phenotype to ⌬SrtA. Immunoblot analysis of fractionated ⌬SrtA cells verified that AS was no longer efficiently incorporated into the cell wall fraction (data not shown) (13).…”
Section: Resultsmentioning
confidence: 92%
“…Introduction of the empty vector did not restore the aggregation phenotype to ⌬SrtA. Immunoblot analysis of fractionated ⌬SrtA cells verified that AS was no longer efficiently incorporated into the cell wall fraction (data not shown) (13).…”
Section: Resultsmentioning
confidence: 92%
“…This RIVET screen and a recent transposon mutagenesis study also undertaken by our group (32) both focused on genetic determinants in the core genome of E. faecalis. While the former study required the use of a microtiter plate biofilm assay, the RIVET study enabled us to use a submerged-coupon system previously shown to support the robust formation of E. faecalis biofilms with distinctive three-dimensional architecture and abundant production of extracellular matrix (18). We suspect that this may account for the fact that many more predicted biofilm determinants were identified in the RIVET screen.…”
Section: Discussionmentioning
confidence: 99%
“…The high polysaccharide content of the endothelial glycocalyx interacts poorly with the commonly used postfixation stains. As a result, the endothelial glycocalyx scatters few electrons and is indistinguishable from its environment in conventionally processed samples for transmission electron microscopy (TEM) (24). Thus, even if the pretreatment of the sample maintains endothelial glycocalyx integrity, an additional staining or preservation is required for the visualization of the glycocalyx in TEM.…”
Section: Studying the Endothelial Glycocalyxmentioning
confidence: 99%